Boundary Works as a Mechanism For Forming Collective Identity in The Indonesian Middle Class Muslim Social Piety Movement - Saputra, Sahran; Ishomuddin; Wahyudi; Saleh, Arifin (Ilomata International Journal of Social Science, 2024)
Indonesia's title as the most generous country in the world is supported by the strengthening spirit of social piety movements among the Muslim middle class. Social piety movements are of course also supported by the power of the social movement's collective identity in forming the basis that provides the "structure," foundation for engagement, and guidance for individual participation in its expansion. Unfortunately, the strong link between the development of collective identity in social movement groups has not been explained by previous studies. The aim of this research is to describe how the boundary work mechanism contributes to the development of collective identity in the Muslim middle class social piety movement in the Tangan di Atas (TDA) community. Using qualitative descriptive research, the research was conducted over a period of one year (December 2022-December 2023) and describes the actors and boundary work mechanisms in forming collective identity. The researcher conducted in-depth interviews with several subjects who were administrators as well as members of the TDA community to explore variations in their experiences related to the social piety movement they engage in. Meanwhile, with a phenomenological approach, researchers explore the role of individual knowledge, thoughts and feelings or internal aspects or individual subjectivity. The results of this research show that there are several aspects that can be used to view boundary works as a mechanism for forming the collective identity of social piety movements in the TDA community; shared values ​​and principles, joint activities, mutual recognition and appreciation, and establishing relationships with external parties.